Pengaruh Supervisi terhadap Kedisiplinan dan Distribusi Guru pada Jenjang Pendidikan Dasar di Kecamatan Pulau Merbau - Robisah Robisah; Ramdhan Witarsa; Nurmalina Nurmalina (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
Academic supervision and managerial supervision are two things that must be done by school principals in carrying out their main tasks and functions at school. This research aims to measure how much influence the supervision carried out by the principal has on the discipline and distribution of teachers at the primary education level in Pulau Merbau sub-district, Meranti Islands district. The method used in this research is a quasi-experimental method. The data collection technique used was disciplinary observation and teacher distribution. The research instruments used were disciplinary observation sheets and teacher distribution. The research results show that supervision by the principal has a significant effect on the discipline and distribution of teachers at the primary education level in Merbau Island sub-district, Meranti Islands district. This discipline and distribution of teachers is reflected in research results that the existing distribution of teachers is not ideal for producing disciplined teachers. It is necessary to increase the number of teachers by 5 people so that teacher discipline can increase. The sub-district area coordinator for the education sector needs to immediately fulfill the required teacher distribution so that teacher discipline can increase and so that students can be served well.